¿Recordar o pasar página? 1936 en la(s) memoria(s) del nacionalismo vasco - José Antonio Rubio Caballero (Cahiers de Civilisation Espagnole Contemporaine)
The memory is not alone a reproduction of the past, but also a subjective representation of experience. In order to show this potentiality, this article studies how two branches of Basque nationalism (pnv and eta), in the 1960´s and 1970´s, produced different historical memories about the Second Republic and Spanish Civil War.